Effects of Bac-D on Total Aerobic Bacteria Naturally Found on Broiler Breeder Eggs - Lowman , Z.S.; Parkhurst, C.R. (International Journal of Poultry Science, 2013)
Hatchery sanitation is of the utmost importance in the poultry industry and may have drastic economic effects within a company. It has been shown that eggs with increased total aerobic bacterial counts may cause a decrease in hatchability, performance and growth, as well as a decrease in overall chick quality. Several methods have been utilized to decrease bacterial load on the exterior surface of the egg such as the use of: hydrogen peroxide, quaternary ammonium compounds, antibiotics and UV light exposure. Many disinfectants may effectively sanitize the egg; however, they have detrimental effects on the developing embryo due to the removal of the cuticle, allowing increased moisture loss from the egg. Benzalkonium chloride has been effectively used as a first aid antiseptic for humans. Bac-D, a novel disinfectant with benzalkonium chloride utilized as the active ingredient. Bac-D is a safe, potential substitute to harsh chemicals. In this trial, eggs were sprayed with the same volume of either Bac-D or water. Eggs were sampled at 3 different time points after spray (0, 1.5, or 3 h). At the culmination of each time point, a portion of the eggs was inoculated with an endogenous bacterial inoculum. Eggs were placed in a bag with 1% PBS and the rinsate was promptly plated on TSA (Tryptic Soy Agar). There were significant decreases (p